The Impact Of Size And Other Income On Systemic Risk In Indonesia - Aditya Kristianto Marjono; Dony Abdul Chalid (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2024)
This research aims to measure systemic risk, especially in the banking system, between 2018 and 2022. In this research, the measurement method used is SRISK, which aims to measure the potential capital shortage of a bank when there is pressure on the market. The lack of capital from a bank, which is an individual risk for a bank, also poses the potential for a contagious threat which could end up becoming a systemic risk in the banking system in Indonesia. This research shows that several banks, through SRISK calculations, have the potential for capital shortages when market pressure occurs, especially from 2019 to 2022. In this research, bank size and non-interest income are essential factors in systemic risk in the banking system. Meanwhile, business complexity does not affect systemic risk in Indonesia.